Pengaruh Kompensasi, Beban Kerja dan Motivasi Terhadap Kinerja Karyawan - Aditiawati, Evita; Parashakti, Ryani Dhyan (Lentera Ilmu Nusantara, 2023)
Human Resources (HR) are individuals who work as movers of an organization, both institutions and companies and function as assets that must be trained and developed capabilities. The phenomenon in this study is the problem of employee performance which has an impact on decreasing sales levels. Based on the observations of researchers in the field that the decline in employee performance is caused by several things, namely compensation, motivation and workload. The purpose of this study is to analyze the effect of work compensation on employee performance. To analyze the effect of workload on employee performance. To analyze the effect of work motivation on employee performance. In this research proposal using quantitative methods. Data collection using questionnaires, a number of questions were made to be filled out by respondents. This research is classified as associative research, which is research that looks for causal relationships or influences, namely the relationship between the independent variable (X) and the dependent variable (Y). The population in this study is all employees who work PT. Karya Sejati Indonesia numbered 75 people. The sampling technique used is saturated sampling, that is, the number of samples used as a whole. The method used in this study is to use the Partial Least Square (PLS) method. Based on the results of Compensation has a positive and significant effect on employee performance. Workload does not affect employee performance so further research is needed.And work motivation has a positive and significant effect on performance.